Mutational analysis of BRCA1 and BRCA2 in northwest Chinese breast cancer patients - Wang, Ting; Zhang, Juliang; Xiao, Jingjing; Huang, Meiling; Li, Nanlin; Ling, Rui (Translational Cancer Research, 2019)
Background: BRCA1 and BRCA2 are the most well-known susceptibility genes in breast cancer, indicating high-risk breast cancer families and influencing both treatment options. However, data of BRCA mutation in Chinese breast cancer population was limited. Here we explored the BRCA1/2 mutation status and analyzed their clinicopathological relationships among breast cancer patients with high hereditary risk in northwest China. Methods: Breast cancer patients admitted to Xijing Hospital, between November 2015 and May 2016, with high hereditary risk were recruited. Fresh peripheral venous blood samples were collected for BRCA1/2 gene screening. Risk factors for BRCA1/2 mutations were studied via single-factor analysis and multivariable logistic analysis. Furthermore, we reviewed the literature and discussed the possible mechanism of the mutant genome types. Results: Eighty-two patients were enrolled in the study. Twenty (24.4%) of them were found with BRCA1/2 mutation, including 8 BRCA1 mutation and 13 BRCA2 mutation. BRCA1 and BRCA2 co-mutation was observed in only one case. The mutant genome types included pathogenic variant (4/82), potential pathogenic variant (4/82), beneficial mutations (8/82), and chemotherapy sensitivity-related mutations (5/82). Prognosis-related mutations were enriched in BRCA2 gene, while drug-sensitive related mutations were always observed in BRCA1 gene. Multiple logistic analysis showed that HER2 [odds ratio (OR) 4.58; 95% confidence interval (CI), 1.182–17.74; P=0.028) might be independent factor for BRCA1/2 mutation. Conclusions: The incidence and feature of BRCA1/2 mutation in our center was similar to that in other regions. HER2 expression was independent factor for BRCA1 and BRCA2 mutation. BRCA2 T/-, BRCA2 A/-, BRCA2 G/- and BRCA2 C/-mutation subtypes might be potential harmful mutations for Chinese breast cancer population.